The impact of Muslim football players on the dissemination of Islamic values in Arab Societies - Mahmoud Al Ali, Jasim Abdulla Ramadan; Mahmoud Al Zitawi, Diaya Ud Deen Deab (Journal of Islamic, Social, Economics and Development, 2025)
Football is considered one of the most popular and influential sports in the Arab world, playing a significant role in shaping the cultural and social identity of communities. This study addresses the research problem of how Muslim football players influence the dissemination of Islamic values and enhance cultural and religious identity within Arab societies. The primary objective of this research is to analyze the role of Muslim football players in promoting Islamic values such as honesty, integrity, humility, and commitment to prayer and fasting, and how this commitment can contribute to building a more cohesive and stable society. This role is underscored by the impactful presence of these players in inspiring Muslim youth and reinforcing cultural and religious identity by serving as role models both on and off the field. The research also discusses the importance of dialogue and constructive interaction between players and fans in improving mutual understanding of Islamic values and promoting peaceful coexistence among various social groups. The study will rely on case studies and analysis of the behaviors of Muslim players through a review of relevant literature, as well as conducting interviews with players and fans, and examining the impact of commitment to Islamic values on their interactions with the community and the audience. Analytical methods will also be employed to assess the impact of these practices on enhancing the public image of Islam and Muslims in Arab societies. This research aims to demonstrate how the commitment of Muslim football players to religious values directly affects the proliferation of these values within society, contributes to enhancing understanding among different cultural and religious groups, thereby fostering peaceful coexistence. The research includes proposing a practical model that can be replicated in other sports and social fields, in addition to improving the public perception of Muslim players and raising awareness of the importance of adhering to religious and ethical values in achieving professional and personal success. Furthermore, the study aims to promote a deeper understanding of the role that Muslim athletes play in building communities and enhancing cultural understanding.